The Influence of Binder Rheological Properties on Asphalt Mixture Permanent Deformation - Marcin Gajewski; Dariusz Sybilski; Wojciech Bańkowski (The Baltic Journal of Road and Bridge Engineering)
The main goal of this paper is to propose the performance parameter for binder which is good for quality prediction of asphalt mixture in frame of resistance to permanent deformation (rutting). Additionally, correlation between, proposed by the authors, repeatable shear creep-recovery test carried out on binder and bituminous mixture rutting test is under evaluation. The results are analysed and correlation between the proposed functional parameter and rut depth is shown. Thanks to that it is possible to claim that expensive rutting test procedure can be assisted with simple test carried out in dynamic shear rheometer at the initial mix design procedure.